Response of Ozone to a Gravity Wave Process in the UTLS Region Over the Tibetan Plateau - Chang, Shujie; Sheng, Zheng; Zhu, Yanwei; Shi, Weilai; Luo, Zhixian (Frontiers in Earth Science, 2020)
In this paper, ERA5 reanalysis data from the European Center for Medium-Range Weather Forecasts and the Weather Research and Forecasting (WRF) mesoscale model are used to compare and simulate a topographic gravity wave event that occurred over the Tibetan Plateau between 18:00 on 3 May 2014 and 00:00 on 4 May 2014. The stratosphere–troposphere exchange (STE) process and its detailed characteristics during the gravity wave event are presented. The response of the upper troposphere and lower stratosphere (UTLS) ozone to the gravity wave is discovered from the perspective of the gravity wave dynamic process. The results show that the gravity wave structure between 90°E and 100°E had a westward tilt with height. From 19:00 to 21:00 the gravity waves decayed and from 22:00 to 23:00 their shape gradually blurred. Meanwhile, there was a response of the ozone mixing ratio in the UTLS over the Tibetan Plateau to the gravity waves breaking. After 21:00, this wave process caused the STE, as air from the stratosphere with a greater ozone concentration was injected into the upper troposphere, leading to rapidly increased ozone concentration there.